Role of graphene oxide in support layer modification of thin film composite (TFC) membrane for forward osmosis application - Wan Nur Syuhada Wan Ata,; Ang, Wei Lun; Abdul Wahab Mohammad, (Penerbit Universiti Kebangsaan Malaysia, 2019)
In this work, the effect of graphene oxide (GO) incorporation into the membrane support layer towards the performance of thin-film composite (TFC) membrane was investigated. The support layer was fabricated by phase inversion method with the incorporation of GO as hydrophilic nanoparticles. Next, the active polyamide layer was formed on the membrane support layer via interfacial polymerization between trimesoyl chloride (TMC) and m-Phenylenediamine (MPD). The cross-section images from Field-Emission Scanning Electron Microscope (FESEM) showed the presence of active polyamide layer on the surface of TFC membrane while the FTIR results indicated the existence of bands associated with the amide linkages. The initial study showed that an optimal amount of GO (0.5 wt%) incorporation into the polymer substrate resulted in favourable improvement in TFC membrane performance. The physical and chemical properties of GO helps in enhancing the water transport through the membrane polymer matrix and thus contributing to higher permeate flux. The TFC-FO membrane incorporated with GO showed 44% improvement in terms of water flux (3.72 compared to 2.09 Lm-2 h-1 for pure PSf membrane) and minimal improvement in reverse solute diffusion (0.02 compared to 0.03 g m-2 h-1 for pure PSf membrane). Thus, this study showed that small addition of GO nanoparticles into the membrane support layer leads to an increase in performance of TFC membrane for FO application.